2020
DOI: 10.1111/cas.14677
|View full text |Cite
|
Sign up to set email alerts
|

Decreased alpha‐1,4‐linked N‐acetylglucosamine glycosylation in biliary tract cancer progression from biliary intraepithelial neoplasia to invasive adenocarcinoma

Abstract: Biliary tract cancer (BTC) is typically lethal due to the difficulty of early stage diagnosis. Thus, novel biomarkers of BTC precursors are necessary. Biliary intraepithelial neoplasia (BilIN) is a major precursor of BTC and is classified as low or high grade based on cell atypia. In normal gastric mucosa, gastric gland mucin‐specific O‐glycans are unique in having α1,4‐linked N‐acetylglucosamine (αGlcNAc) attached to MUC6. Previously, we reported that αGlcNAc functions as a tumor suppressor of differentiated‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Because decreased αGlcNAc expression was also observed in benign lesions, such a decrease may occur during the very early stage of tumour progression. This phenomenon was also observed in IPMN-IPMNAIC, PanIN-IDAC, BilIN-IAC, and LEGH-GAS sequences [10,11,17]. We have previously reported that gastric adenocarcinoma develops spontaneously in A4gnt-deficient mice [5].…”
Section: Figsupporting
confidence: 54%
See 3 more Smart Citations
“…Because decreased αGlcNAc expression was also observed in benign lesions, such a decrease may occur during the very early stage of tumour progression. This phenomenon was also observed in IPMN-IPMNAIC, PanIN-IDAC, BilIN-IAC, and LEGH-GAS sequences [10,11,17]. We have previously reported that gastric adenocarcinoma develops spontaneously in A4gnt-deficient mice [5].…”
Section: Figsupporting
confidence: 54%
“…MUC6 and αGlcNAc expression was reduced with OPMT progression. The phenomenon was also observed in IPMN-IPMNAIC and PanIN-IDCA sequences in pancreatic tumours [10], the BilIN-IAC sequence in biliary tract tumours [11], and the LEGH-GAS sequence in uter-Expression scores of MUC6 and αGlcNAc at each grade of OPMTs. The expression score of αGlcNAc is significantly lower than that of MUC6 at all tumour grades.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Decades of research have demonstrated that aberrant protein glycosylation often occurs in the development of tumors, and it has been shown that specific tumor-associated glycans are expressed in the precursor lesions of different types of cancer, which makes them potentially powerful early diagnosis markers ( Oliveira-Ferrer et al, 2017 ; Liu et al, 2018 ; Okumura et al, 2020 ; Schedin-Weiss et al, 2020 ; Zhang et al, 2020 ). Glycomic and glycoproteomic analysis of blood samples have shown that glycans or glycan profiles could be used as candidate biomarkers to distinguish EC from controls and potential predictors of disease progression ( Yehia et al, 2009 ; Hammoud et al, 2010 ; Mohanty et al, 2012 ; Song et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%